To find the inverse of the function \( f(x) = 5(x - 9) \), we can follow these steps:
-
Replace \( f(x) \) with \( y \): \[ y = 5(x - 9) \]
-
Swap \( x \) and \( y \): \[ x = 5(y - 9) \]
-
Solve for \( y \):
- First, divide both sides by 5: \[ \frac{x}{5} = y - 9 \]
- Then, add 9 to both sides: \[ y = \frac{x}{5} + 9 \]
-
Replace \( y \) with \( f^{-1}(x) \): \[ f^{-1}(x) = \frac{x}{5} + 9 \]
Therefore, the correct response is: \[ f^{-1}(x) = \frac{x}{5} + 9 \]
In text form, this is the same as saying: f inverse of x is equal to x over 5 plus 9.